The Perseverance of Life: Exploring the Struggle for Existence in Hemingway's The Old Man and the Sea - Ghimire, Din Prasad (International Research Journal of Parroha, 2023)
Ernest Hemingway's classic novel, "The Old Man and the Sea," is a powerful exploration of the human spirit's unyielding determination to find purpose and meaning in a seemingly indifferent and absurd world. The protagonist, Santiago, emerges as a symbol of hope and resilience in the face of existential challenges. This abstract delves into Santiago's unwavering courage and enduring patience, which guide him towards a triumphant victory in his life. Santiago's journey is a rebellion against the inherent absurdity and meaninglessness of existence, a struggle to carve out his own purpose in an indifferent universe. His character epitomizes the heroism, stoicism, and humanism necessary for preserving one's existence amidst the chaos of life. Through Santiago's relentless battle with the marlin and the elements of the sea, Hemingway artfully crafts an allegory for the broader human experience. Santiago's struggle symbolizes the fundamental themes of heroism, as he confronts insurmountable odds; stoicism, as he endures relentless hardship and loss with unshakable composure; and humanism, as he forms a deep connection with the natural world and ultimately emerges as a triumphant figure in the face of life's existential challenges. "The Old Man and the Sea" remains a timeless literary work, offering profound insights into the human condition and the enduring quest for meaning in a world that often appears absurd and indifferent. Santiago's indomitable spirit serves as an inspiration to all who face the struggle for existence against the backdrop of the universe's inherent ambiguity and meaninglessness.